ANALISIS BIBLIOMETRIK TREN PENELITIAN PADA PENERAPAN PAJAK KARBON MENGGUNAKAN VOSVIEWER - Richi Guali Padang; Rachmat Agus Santoso; Fitriana Fitriana (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to describe the trend of research on carbon tax, focusing on article identification including the year of publication, the countries that produce the most articles, the articles with the most citations and related topics. This study uses bibliometric analysis with VOSviewer software based on Scopus data, covering 206 articles published from 2015-2025. Data was collected using the keyword “Carbon Tax” to be analyzed for identification. The results found that the number of publications on carbon tax fluctuated each year, with 2024 being the most published year with 37 articles. China and the United States lead in the number of articles and citations, followed by India and other countries. The article "Retailer-driven carbon emission abatement with consumer environmental awareness and carbon tax: Revenue-sharing versus Cost-sharing" was the most cited with 359 citations. Research trends on carbon taxes focus on emissions control and the environment, emissions trading and public policy, economic analysis and computational modeling, sustainability policy and supply chains and environmentally sustainable renewable energy. The pattern of research conducted by researchers shows that research on carbon tax now focuses on carbon emission trading, energy supply chain, transition to renewable energy as well as more technical aspects such as carbon accounting, sensitivity analysis and energy utilization in achieving net zero emission